Subsurface Sediment Distribution in The Sumba Waters, East Nusa Tenggara - Putra, Purna Sulastya; Nugroho, Septriono Hari (Oseanologi dan Limnologi di Indonesia, 2017)
Marine geological survey of the Ekspedisi Widya Nusantara 2016 was conducted in the Sumba Waters on 4 to 26 August 2016 using Â Baruna Jaya VIII research vessel. The aim of this survey was to reveal the type and characteristics of the subsurface sediments of the Sumba Waters. A total of 13 samples were taken from the different depth in the subsurface bottom of the sea using grabbing methode with box corer. Grain size analysis were conducted using Mastersizer 2000 to understand the characteristics and the sediment type distribution. In general, the type of the subsurface sediment in the Sumba Waters is ranging from medium to very coarse sandy silt. Distribution of the subsurface sediments is correlated to depths. Grain size of the sediments in the Sumba Strait is coarser than in the western and southern of Sumba Island that directly connected to the Indian Ocean. Distribution of the subsurface sediment showing that the sediment, which are distributed further away from the coast is poorly sorted. The deposition of the subsurface-sea sediment is interpreted to represent a calm, and slow sedimentation mechanism under uniform suspension process.